2018
DOI: 10.7554/elife.38268
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of developmental and molecular factors underlying release heterogeneity at Drosophila synapses

Abstract: Neurons communicate through neurotransmitter release at specialized synaptic regions known as active zones (AZs). Using biosensors to visualize single synaptic vesicle fusion events at Drosophila neuromuscular junctions, we analyzed the developmental and molecular determinants of release probability (Pr) for a defined connection with ~300 AZs. Pr was heterogeneous but represented a stable feature of each AZ. Pr remained stable during high frequency stimulation and retained heterogeneity in mutants lacking the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
151
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(172 citation statements)
references
References 123 publications
(259 reference statements)
20
151
1
Order By: Relevance
“…This phenotype was never observed in controls 496 (average protrusions per MN1-Ib NMJ: UAS-TeTXLC: 0, n=14; MN1-Ib GAL4: 0, n=25; MN1-497 Ib>TeTXLC: 7.2 ± 2.4, n=16, F (4, 83) = 9.921, p=0.0001, Figure 11D). Similar filopodial-like 498 protrusions were described previously at early 1 st instar NMJs during the initial stages of synapse 499 formation in wildtype animals, but never at mature 3 rd instar NMJs (Akbergenova et al, 2018). 500 Such protrusions were not observed in silenced Is motoneurons or in Ib motoneurons following Is 501 silencing ( Figure 11A-D), indicating MN1-Ib and MNIs react differently to changes in their own 502 activity.…”
Section: Ib Ablation Resulted In M1 Having No Synaptic Innervation (4supporting
confidence: 69%
See 2 more Smart Citations
“…This phenotype was never observed in controls 496 (average protrusions per MN1-Ib NMJ: UAS-TeTXLC: 0, n=14; MN1-Ib GAL4: 0, n=25; MN1-497 Ib>TeTXLC: 7.2 ± 2.4, n=16, F (4, 83) = 9.921, p=0.0001, Figure 11D). Similar filopodial-like 498 protrusions were described previously at early 1 st instar NMJs during the initial stages of synapse 499 formation in wildtype animals, but never at mature 3 rd instar NMJs (Akbergenova et al, 2018). 500 Such protrusions were not observed in silenced Is motoneurons or in Ib motoneurons following Is 501 silencing ( Figure 11A-D), indicating MN1-Ib and MNIs react differently to changes in their own 502 activity.…”
Section: Ib Ablation Resulted In M1 Having No Synaptic Innervation (4supporting
confidence: 69%
“…We and others have observed similar filopodial-like extensions at newly forming NMJ 569 connections in late embryos and early 1 st instar larvae (Halpern et al, 1991;Broadie and Bate, 570 1993;Ritzenthaler et al, 2000;Ritzenthaler and Chiba, 2003;Kohsaka and Nose, 2009;571 Akbergenova et al, 2018). These presynaptic filopodial processes contain elevated levels of the 572 Cacophony (Cac) N-type Ca 2+ channel and interact with GluRIIA-rich myopodia, with some 573 progressing to form new synapses during early development (Akbergenova et al, 2018). Due to 574 the lack of reinforcement signals caused by absence of synaptic activity in silenced MN1-Ib 575 motoneurons, we hypothesize these processes fail to properly drive AZ assembly and new synapse 576 formation.…”
Section: Ib Ablation Resulted In M1 Having No Synaptic Innervation (4mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that presynaptic release positively correlates with AZ-size 3, 42-45 . Therefore, we expected that the increase of AZ-BRP/Unc13A observed upon PhTx treatment would functionally increase presynaptic release (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Membrane‐delimited ApSrc‐gCAMPS6 was made first by cutting out the sequence encoding GCaMP6f () with Bgl II and Not I and inserting into the compatible sites BamHI and EagI in the pNEX3 vector to generate pNEX3‐GCaMP6f. Similar to previous membrane‐delimited GCaMPs (Shigetomi et al ; Akbergenova et al ), we used the first 34 amino acids of Aplysia Src (NP_001191639.1) containing putative myristoylation and palmitoylation sites inserted in front of the GCaMP sequence. The sequence was purchased as a gBLOCK (IDT) with HinDIII and XbaI sites and inserted into pNEX3‐GCaMP6f at the same sites.…”
Section: Methodsmentioning
confidence: 99%